2016
DOI: 10.1057/s41292-016-0033-0
|View full text |Cite
|
Sign up to set email alerts
|

Fringe biotechnology

Abstract: Recent amateur and alternative uses of wet laboratory biology techniques have been called by many names. However, none of the terms currently in use include institutional, entrepreneurial and amateur engagements in biotechnology with non-scientific aims. In this article, the author introduces the more comprehensive concept of fringe biotechnology. While 'DIYbio' has in recent years become a term that covers a wide range of hobbyist approaches to biotechnology, it still excludes several other alternative biotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…Many news outlets reported that DIY and maker communities were harnessing existing digital platforms and creating new ones to co-produce and disseminate designs of PPE, ventilators and other medical equipment, even a vaccine. With regard to the boundary work around science, DIY science and the maker movement can be understood as examples of “fringe science” (Vaage, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many news outlets reported that DIY and maker communities were harnessing existing digital platforms and creating new ones to co-produce and disseminate designs of PPE, ventilators and other medical equipment, even a vaccine. With regard to the boundary work around science, DIY science and the maker movement can be understood as examples of “fringe science” (Vaage, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Through his original framework of “boundary work,” Gieryn ( 1999 , p. 2) argued that “newspapers … and cyberspace are fat with credibility contests,” whereby “experts bearing science are enlisted everywhere to defend all sides and all opinions with putatively objective, reliable, and accurate facts.” The notion of “credibility contests” is central to Gieryn's ( 1999 ) conceptualization of “boundary work” around science, which takes place when the nature and content of “real science” is discursively demarcated from various categories of science “posers” and “fringe science,” such as “pseudoscience” or bad science but also, importantly, amateur science. Mainstream science is often pitted against the fringe, where “fringe science” can be understood to capture a range of heterogenous activities at the outskirts of institutionally legitimated science, forming a liminal sphere at the edges of “science proper” (Vaage, 2016 ). Such fringe endeavors may aim at “shifting the current ideas of who is entitled to conduct research in the life sciences, and how such research should be done” (Vaage, 2016 , p. 127).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods and technology would also have to be simplified so that a home cook understands how to safely produce cultured products for their family. Though DIY biology has become the interest of a small but dedicated network of biomakers, the large majority of cellular agriculture engineering projects are still undertaken by teams with relevant college degrees and training (Landrain et al, 2013;Seyfried et al, 2014;Vaage, 2017). A Library of Things model could address some knowledge gaps by hosting public seminars and swaps of recipes and cell culture at the library.…”
Section: Availabilitymentioning
confidence: 99%
“…Synbio is through its focus on standardisation, 'deskilling' and open source one of the more accessible fields of science and has been important in opening up biology to do-it-yourself (DIY) practices. DIY biology (DIYbio) is a non-institutional phenomenon of citizens working with biology, sometimes with a 'hacker' mentality [26,42]. Indeed, also within the institutional synbio communities it is not uncommon to refer to one's work as 'hacking life', which may, like tinkering, be a more appropriate analogy than rational design [26].…”
Section: Biological Machines In Synthetic Biologymentioning
confidence: 99%